Targeted RNAi screen identifies transcriptional mechanisms that prevent premature degeneration of adult photoreceptors - Escobedo, Spencer E.; McGovern, Sarah E.; Jauregui-Lozano, Juan P.; Stanhope, Sarah C.; Anik, Paul; Singhal, Kratika; DeBernardis, Ryan; Weake, Vikki M. (Frontiers in Epigenetics and Epigenomics, 2023)
Aging is associated with a decline in visual function and increased prevalence of ocular disease, correlating with changes in the transcriptome and epigenome of cells in the eye. Here, we sought to identify the transcriptional mechanisms that are necessary to maintain photoreceptor viability and function during aging. To do this, we performed a targeted photoreceptor-specific RNAi screen in Drosophila to identify transcriptional regulators whose knockdown results in premature, age-dependent retinal degeneration. From an initial set of 155 RNAi lines each targeting a unique gene and spanning a diverse set of transcription factors, chromatin remodelers, and histone modifiers, we identified 18 high-confidence target genes whose decreased expression in adult photoreceptors leads to premature and progressive retinal degeneration. These 18 target genes were enriched for factors involved in the regulation of transcription initiation, pausing, and elongation, suggesting that these processes are essential for maintaining the health of aging photoreceptors. To identify the genes regulated by these factors, we profiled the photoreceptor transcriptome in a subset of lines. Strikingly, two of the 18 target genes, Spt5 and domino, show similar changes in gene expression to those observed in photoreceptors with advanced age. Together, our data suggest that dysregulation of factors involved in transcription initiation and elongation plays a key role in shaping the transcriptome of aging photoreceptors. Further, our findings indicate that the age-dependent changes in gene expression not only correlate but might also contribute to an increased risk of retinal degeneration.